Arte, arti e politica tra ispirazione e tirocinio: gli irriducibili binomi di Mussolini - Frosini, Fabio (Laboratoire italien, 2023)
With the alternative between art in the singular and the arts in the plural, in relation to politics, two distinct tracks of interpretation within Mussolini’s thought are highlighted: that of politics as an “art” and that of the link between the various arts and political power, that is, the link between the artistic character of politics and the political character of the arts and culture in general. The two themes are intertwined: the first revolves around the nature of politics, the second refers to the civil and social vocation and function of culture and art in particular. It is also demonstrated that the ideas of politics as art and arts as politics find their point of encounter in the fact that art is for Mussolini always linked to a broader idea of craftsmanship, which defines art in a technical-instrumental and productive sense, but also in a reflective sense. In light of this fact, considerations are introduced about the concept of “organisation” in relation to both culture and politics.